2023
DOI: 10.1002/ejoc.202201470
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Catalytic Approaches Employing α,β‐Unsaturated Imines

Abstract: Nitrogen-containing heterocyclic compounds have consistently been a noticeable center of attention due to their significant utilization in the domain of synthetic organic chemistry, agrochemicals, and pharmaceuticals. α,β-Unsaturated imines or conjugated imines provide a lot of significant cyclic as well as acyclic products through reacting with a versatile family of compounds. This review summarizes the recent advances in enantioselective reactions of α,β-unsaturated imines by using synthetic methodologies fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 122 publications
(164 reference statements)
0
6
0
Order By: Relevance
“…Such imines or conjugated imines provide a lot of significant cyclic as well as acyclic products through diverse reactivity with a versatile family of compounds [14,15]. The literature revealed that α,β-unsaturated imines can be prepared the following reactions by (i) heat elimination of imino-alcohol skeleton; (ii) allyl cation-mediated Schmidt between azides and alcohols; (iii) aza-Wittig reaction of αketophosphonates and trimethyl phosphazenes and (iv) dehydrogenative coupling between primary allylic alcohol and a primary amine [16]. Recently, Sc(OTf)3-catalyzed annulations reactions of vinyl diazoacetates with in situ formation of indole-derived, α,β-unsaturated imines for the preparation of cyclopenta[b]indoles has been reported [17].…”
Section: Green and Efficient Chemo-selective Synthesis Of Chalconementioning
confidence: 99%
“…Such imines or conjugated imines provide a lot of significant cyclic as well as acyclic products through diverse reactivity with a versatile family of compounds [14,15]. The literature revealed that α,β-unsaturated imines can be prepared the following reactions by (i) heat elimination of imino-alcohol skeleton; (ii) allyl cation-mediated Schmidt between azides and alcohols; (iii) aza-Wittig reaction of αketophosphonates and trimethyl phosphazenes and (iv) dehydrogenative coupling between primary allylic alcohol and a primary amine [16]. Recently, Sc(OTf)3-catalyzed annulations reactions of vinyl diazoacetates with in situ formation of indole-derived, α,β-unsaturated imines for the preparation of cyclopenta[b]indoles has been reported [17].…”
Section: Green and Efficient Chemo-selective Synthesis Of Chalconementioning
confidence: 99%
“…The benzofuran-derived azadienes have long been regarded as competent four-atom synthons for constructing N-heterocycle scaffolds via catalytic asymmetric [4+n] cyclizations . In this context, a sequential enantioselective α-conjugate addition/cyclization of ynones bearing acidic α-H and benzofuran-derived azadienes, promoted by chiral bifunctional squaramide and DBU catalysis (Scheme b), was envisioned to provide chiral eight-membered N-heterocycles even though it may be challenging to control the chemo- and regioselectivity as the undesired [4 + 2] competing pathway initiated by β-cyclization .…”
Section: Introductionmentioning
confidence: 99%
“…Acyclic α,β-unsaturated imines, which served as an efficient source of four-atom synthons for the construction of nitrogen heterocyclic compounds, have received much attention. 16 Over the past decade, the asymmetric [4 + 1] and [4 + 2] cycloaddition reactions involving acyclic α,β-unsaturated imines have been extensively studied to access structurally diverse five- and six-membered nitrogen-containing heterocycles. 17,18 Recently, these imines have also been utilized in the catalytic [4 + 4] 19 and [4 + 5] 20 cycloaddition reactions.…”
Section: Introductionmentioning
confidence: 99%